Optimum design of RC affordable housing - Fathy, Amr Mostafa Hussein (AUC Knowledge Fountain, 2015)
Efforts have been made to minimize the cost of affordable housing through modular construction, prefabrication, economies of scale and low cost materials. However, there is a gap in the literature regarding the integration of the varying sizes of the units with design optimization to mutually benefit developers and potential residents of affordable homes. This research introduces an optimization model to integrate optimization with ranges of units' dimensions. The model proposed exploits the variations in the reinforced concrete cost versus area through applying several scenarios. Available options are tailored to optimize the reinforced concrete floor cost of housing units through varying the dimensions of the rooms. In addition to this objective, the thesis investigates the sensitivity of selected parameters on the model output. Through these objectives, the model is able to optimize housing units within a specified budget to result in layouts with varying areas where the model would recommend the layout with the least reinforced concrete cost per m2 within the budget range. In addition, it optimizes housing units within a specified area range to result in layouts with varying cost where the model would recommend the layout with the least reinforced concrete cost per m2 in the selected area range. The model has been applied on 2 case studies where it showed promising results. The research was able to optimize the cost for a given area or increase the area for a given cost. For example, it was able to decrease the cost by 15% for the same area. These percentages are based on the selected examples. Different savings may be achieved with other layouts. However, this is dependent largely on the initial design and dimensions of the unit.